Coping with stress among preschool children and associations with anxiety level and controllability of situations. (27th March 2014) - Yeo, Kelly; Frydenberg, Erica; Northam, Elizabeth; Deans, Janice
Abstract The primary aim of this study was to describe how preschoolers (4–5 years old, N = 94) cope with stress based on parent ratings on the Children's Coping Scale Revised. A second aim was to investigate how coping in preschoolers may be associated with the anxiety level of the child and controllability of the stressor, as measured by parent ratings on the Spence Preschool Anxiety Scale and children's coping in two different situations of varying controllability. Three distinct dimensions of coping were identified—positive coping, negative coping–emotional expression, and negative coping–emotional inhibition. As predicted, preschoolers rated higher on anxiety were more likely to engage in negative forms of coping while less anxious preschoolers were more likely to engage in a positive form of coping. This suggests an early pattern of maladaptive coping among more anxious children. Contrary to adult and adolescent models, preschoolers in general were more likely to use negative coping in a more controllable situation and to use positive coping in a less controllable situation. Possible explanations for these findings and suggestions for future research are proposed.